PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA RESTAURANT MY BENTO - Suleman, Dede (www.bsi.ac.id, 2014)
Improving the quality of services offered by the company to the attention of management. This is because the quality of service can be used as a tool to achieve competitiveadvantage. The purpose of this study conducted to determine the influence of service quality on customer satisfaction on restaurant My Bento japanese Fast food. This study uses primary data by conducting research directly in the field with data collection techniques are used questionnaires or sheet statement to the 100 respondents, and secondary data that can support the research, are for methods of analysis and hypothesis testing using simple linear regression. Based on the coefficient of determination can be concluded that the effect of service quality on satisfaction at fast-food restaurants My Bento . Based on calculations with simple linear regression formula obtained results Y = 0.575X + 5.028 and hypothesis test results of 17 989 t-test and t-table 1.66, then so determination obtained yield was 76.50%. Based on these results it can be concluded that significant. Significant here means Ha Ho accepted and rejected, which means there is the influence of the variable x (quality of service) of the variable y (customer satisfaction) and Quality of Service makes an influence on consumer satisfaction was 76.50% while the rest of 23:50% obtained by other factors or variables that is unknown and is not included in this regression analysis. Keywords: Quality of Service and Customer Satisfaction